PERTANGGUNGAN RESIKO MENURUT FATWA DSN-MUI NO. 39 TAHUN 2002 TENTANG ASURANSI HAJI: STUDI PADA KEMENAG KOTA BANDA ACEH - Mutia Martuna Ningsih; Armiadi Musa; Azmil Umur (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
This article aims to analyse the practice of Hajj insurance at the Ministry of Religious Affairs of Banda Aceh City with a review according to Fatwa DSN-MUI Number 39 of 2002 concerning Hajj insurance. The role of the government in the management of Hajj insurance and the mechanism for submitting Hajj insurance claims are analysed. The problems in this study focus on how is the practice of Hajj insurance for pilgrims and the mechanism for submitting Hajj insurance claims at the Ministry of Religious Affairs of Banda Aceh City with relevance to the DSN-MUI Fatwa Number 39 of 2002 concerning Hajj Insurance Practices. The primary data is gathered from interviews and observations. While secondary data is obtained from the results of research related to this study. The results showed that, first, the insurance practice at the Ministry of Religious Affairs of Banda Aceh City is only limited as a facility provider who proposes to the Central Ministry of Religion Office as a policy holder, so that the insurance claim process occurs at the central level and can be confusing for pilgrims. Nevertheless, the Hajj insurance used by pilgrims is considered in accordance with Islamic teachings because it is sharia-based. Second, the mechanism for submitting insurance claims, families can apply for insurance to the provincial ministry of religion office which will then be submitted to the centre while carrying a number of requirements. Some of the requirements include a death certificate (SKK), a statement letter of heirs from the sub-district and the account number of the deceased or heirs. Third, in the review of the DSN-MUI fatwa No.39 of 2002 concerning Hajj insurance, the practice of Hajj insurance that occurs at the Ministry of Religious Affairs of Banda Aceh City is still less than optimal. Hajj pilgrims do not even know at all about the insurance claim process. Especially for pilgrims from the regions, the process of submitting claims is considered difficult to understand. In fact, the heirs of pilgrims often do not know how to submit insurance claims used by pilgrims, the absence of representatives from PT Asuransi Takaful Keluarga in the regions is also an obstacle in the process of submitting claims, so that the families of pilgrims face challenges in submitting claims with a long procedures.